BIOAVAILABILITY ENHANCEMENT OF REPAGLINIDE USING NANO LIPID CARRIER: PREPARATION CHARACTERIZATION AND IN VIVO EVALUATION - KESHARWANI, ROOHI; PATEL, DILIP K.; YADAV, PANKAJ KUMAR (International Journal of Applied Pharmaceutics, 2022)
Objective: The aim of this study to manufacture the prolonged release lipid nanoparticle (Solid lipid nanoparticle and nanostructure lipid carrier) of repaglinide for enhance the oral bioavailability. Methods: Solid lipid nanoparticles (SLN) and Nanostructured lipid carriers (NLC) were prepared by slight modification in the solvent diffusion method. The core material used as cetyl alcohol while blend with oleic acid was used in the preparation of NLC dispersion. Tween 80 were utilized as a Surfactant and lecithin as a cosurfactant in both types of lipid formulation. Lipid nanoparticles were characterized for size distribution, entrapment parameter, zeta potential, surface morphology, in vitro drug release and stability study. Pharmacodynamic study were also performed to evaluate the antidiabetic activity of repaglinide-loaded lipid nanodispersion. Results: It was observed that lipid matrix-based SLN and NLC having significant particle size (157.8±15.8 nm for NLC and 238.4±48.2 nm for SLN dispersion), entrapment efficacy 79.82±0.84% for NLC and 72.04±1.03% for SLN dispersion. Zeta potential report was also clarifying that the formulation is in a stable state for a prolong time. SEM study size distribution of particle as evaluated by Malvern instrument. The formulation was also confirmed to be stable after 180 d of storage, according to the data from the stability study. The in vivo antidiabetic assessment showed that Repaglinide-loaded SLN and NLC dispersion were able to reduce the blood sugar level. Interestingly, in the case of the RPG-SLN, RPG-NLC-I and RPG-NLC-II groups, and the average blood sugar values at all-time intervals were significantly less than that of the basal glucose value (p<0.05). Conclusion: The prepared SLN and NLC dispersion having the ability to control the release and make nano formulation suitable to resolve poor bioavailability of repaglinide.